Pengembangan modul bimbingan pribadi sosial untuk meningkatkan resiliensi Siswa Korban Bullying - Seri Ahmad (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
The objectives of the research are: (1) To discover the description of resilienciesof bullying victims and implementation of social personal guidance, (2) To develop social personal guidance module which is valid, interesting, and practical to improve resiliencies of the students as bullying victims (3) To develop social personal guidance module in improving resiliencies of the students as bullying victims. The study is Research and Development approach or Borg & Gall development model wich had been modified with data collection techniques conducted through questionnaire, scale, and (FGD). The results of the research reveal that (1) Bullying behaviors are still often discovered, it shows that there are many students who were unable to escape from the unfortunate situation, so social personal guidance module to improve resiliencies of the students as bullying victims is very needed in school, (2) The module produced is valid, interesting, and practical based on the assessment conducted by two of Guidance Counseling experts. (3) The implementation of social personal guidance module can improve resiliencies of the students as bullying victims.